Pelayanan Komunikasi Pemerintahan Dalam Pemberitaan Kebijakan Pemerintah Daerah Kepada Stakeholder di Kalimantan Selatan - Sarwani Sarwani (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
This study was conducted in the midst of the lack of studies on local government communication in developing countries. Existing studies tend to attribute performance in this area to central government. The contribution of this study is related to exploring the practice of government communication in the context of local government in countries towards democracy. The author uses the communication of the local government of South Kalimantan Province in its services to stakeholders as a case study. The results of the analysis of various documents, observations and in-depth interviews related to the communication performance of local government in South Kalimantan from January to October 2020 were compiled and analyzed using Miles and Huberman data analysis techniques. In conclusion, the results of the study show that the quality of local government communication is influenced by various factors, both structural and management. Although management factors remain important, in the case of South Kalimantan, structural factors have more influence on local government communications. While the communication performance of local government has not involved active participation from the bottom, it is more elite-oriented than public-oriented. Local government officials are less responsive and still communicate downward, so that the ideas of professionalizing local government communication are still limited to expectations rather than reality. This study recommends that local government communication can be effective if it is participatory, ie has a vision and mission of community empowerment and citizen involvement in participation for local government policy planning and implementation.